PENGEMBANGAN MATERI AJAR TEKS BIOGRAFI BERBANTUAN MEDIA EDUCAPLAY PADA SISWA KELAS X SMK PAB 2 HELVETIA - Muhammad Khoir Pahlepi; Muharrina Harahap (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the process, form, and feasibility of the product of Educaplay-assisted biographical text teaching materials for grade X SMK students. The development process uses the Research and Development (R&D) method of the Borg and Gall model which includes the stages of potential and problems, data collection, product design, validation by material experts and media experts, and design revisions. The resulting product is in the form of biographical text teaching materials that are packaged interactively through the Educaplay platform so that they are more interesting and easier for students to understand. The feasibility of the product was determined through expert assessment with a percentage of 91.07% from material experts and 86.3% from media experts, with an average of 88.6% categorized as very feasible. Thus, the developed product is considered suitable for use in Indonesian language learning in grade X SMK.